INTERRELIGIOUS DIALOGUE: A Possible Response to Ram Janmabhumi Mandir-Babri Masjid Issue - Tellis, Ronald (Asian Horizons, 2011)
The overall view of Indian society is multi-religious, multi-cultural, multi-ethnic and multi-linguistic. Hindus of different traditions, Buddhists and Jains of various schools, Muslims of more than one lineage, Christians of many Churches, different groups of Sikhs and Zoroastrians and several tribal communities live in India side by side, and have done so for many centuries. Of these, Hinduism, Buddhism, Jainism and Sikhism were born and developed in India. There is a strong belief that Christianity arrived in India as early as 52 AD, and that Islam was brought to India towards the end of the seventh century AD. According to the official decennial census of 2001, there were about 827.6 million Hindus (80.5%), 138.2 million Muslims